Aplikasi Penentuan Peserta Pelatihan Di Institut Bisnis Dan Informatika Stikom Surabaya - Zulfikar, Zulfikar; Arifin, Mochammad; Martono, Siswo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Institute of Business and Information STIKOM Surabaya is a campus that has long stood in Surabaya. There’s a lot of employee in this campus, both lecturers and non-lecturers staff. The problems that exist currently happening is Stikom Surabaya still determining employee training by manual. This can lead to less precise training provided to employees. This problem can be solved with the help of using application for determination of traninees. The development of these applications using Software Development Lifecycle (SDLC) models waterfall. The results of testing from this application training resulting determination indicates that the application can assist the company in determining the appropriate training to employees. Determination from application training provides training recommendations to employees in accordance with the disadvantages that these employees have. So that training can be carried out more efficiently and effectively.